Drosophila as a model to study the role of blood cells in inflammation, innate immunity and cancer - Wang, Lihui; Kounatidis, Ilias; Ligoxygakis, Petros (Frontiers in Cellular and Infection Microbiology, 2014)
Drosophila has a blood system with three types of haemocytes which function throughout different developmental stages and environmental stimuli. Haemocytes play essential roles in tissue modelling during embryogenesis and morphogenesis, and also in innate immunity. The open circulatory system of Drosophila makes haemocytes ideal signal mediators to cells and tissues in response to events such as infection, wounding and tumour formation. In this context, Drosophila is now used for screening and investigation of genes implicated in human leukaemia and also in modelling development of solid tumours. This line of research offers promising opportunities to determine the seemingly conflicting roles of blood cells in tumour progression and invasion. This review provides an overview of the signalling pathways conserved in Drosophila during haematopoiesis, haemostasis, innate immunity, wound healing and inflammation. We also review the most recent progress in the use of Drosophila as a cancer research model with an emphasis on the roles haemocytes can play in various cancer models and in the links between inflammation and cancer.